REVERBERATION OF THE MAIN SCENE OF THE BOOK OF DADAM KORKUT IN THE KHOREZM EPIC (American Journal of Interdisciplinary Research and Development, 2024)
The article examines the typological views on the mythological plots of the epic «Kitabi dadam Korkut» in the Khorezm epic. The typological similarity of the characters of Korkut ota, Dapagoz, Saldzhanhotun with alternative symbols in the epics «Gorogly», «Edigo» and «Sayod and Khamro» is highlighted.